Development of an HPLC-UV/Vis method for the determination of dyes in a gasoline sample employing different pre-treatments - Goncalves Trindade, Magno Aparecido [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Matysik, Frank-Michael (Elsevier B.V., 2010)
A simple method was developed for the determination of the dyes Solvent Blue 14 (SB-14), Solvent Orange 7 (SO-7) and Solvent Red 24 (SR-24), based on high-performance liquid chromatography (HPLC) coupled with UV-Vis detection. The dyes were separated employing a reverse phase C-18 column, with gradient elution using a mobile phase containing acetonitrile/water. In conjunction with suitable sample pre-treatment protocols, the method was applied to the quantification of the dyes in gasoline samples. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Solvent Blue 14; Solvent Orange 7; Solvent Red 24; Marker dyes; Petrol